2021
DOI: 10.1016/j.jebo.2021.06.034
|View full text |Cite
|
Sign up to set email alerts
|

Gender heterogeneity of bureaucrats in attitude to corruption: Evidence from list experiment

Abstract: A high level of corruption usually constrains economic development in emerging countries. However, anti-corruption campaigns often fail because the relevant policies need to be implemented by existing corrupt governments. This article studies the extent of bureaucrats' heterogeneity in attitude to the problem of corruption. Due to the sensitivity of direct questions on corruption, we conduct the list experiment among public procurement officials in Russia. We show that female bureaucrats consider corruption to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…While Detkova et al (2021) identified differences in insights on corruption among male and female government officials in Russia, where the women were more aware of its harmful effects on procurement, suggesting their higher probability to support anti-corruption practices while the men were unaffected. They also demonstrated that women were less likely to have high positions despite having almost similar expertise.…”
Section: Studies and Articlesmentioning
confidence: 96%
“…While Detkova et al (2021) identified differences in insights on corruption among male and female government officials in Russia, where the women were more aware of its harmful effects on procurement, suggesting their higher probability to support anti-corruption practices while the men were unaffected. They also demonstrated that women were less likely to have high positions despite having almost similar expertise.…”
Section: Studies and Articlesmentioning
confidence: 96%
“…For example, development economists have used this method to study sexual activity and reproductive behavior in Uganda (Jamison et al 2013), as well as in Cameroon and Cote d'Ivoire (Chuang et al 2021). List experiments have also been used in economics to examine corruption in public procurement in Russia (Detkova et al 2021 Our study is most closely related to Coffman et al (2017), who conducted a list experiment in 2012 to study anti-LGB sentiment using an Amazon Mechanical Turk sample. They showed that the magnitude of anti-LGB sentiment is significantly understated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, development economists have used this method to study sexual activity and reproductive behavior in Uganda (Jamison, Karlan, and Raffler 2013) as well as Cameroon and Cote d'Ivoire (Chuang et al 2021). List experiments have also been used in economics to examine corruption in public procurement in Russia (Detkova, Tkachenko, and Yakovlev 2021) Our study is most closely related to Coffman, Coffman, and Ericson (2017) who conducted a list experiment in 2012 to study anti-LGB sentiment using an Amazon Mechanical Turk sample. They showed that the magnitude of anti-LGB sentiment is significantly understated.…”
Section: Literature Reviewmentioning
confidence: 99%